Soils Laboratory Manual - Moorberg, Colby J.; Crouse, David A. (Open textbook library., 2017)
The Soils Laboratory Manual, K-State Edition is designed for students in undergraduate, introductory soil science courses, and highlights the many aspects of soil science, including: soil genesis and classification, soil physical properties, soil-water interaction, soil biology, soil chemistry, and soil fertility. The lab manual includes 15 different laboratories, each one starting with an introduction and pre-lab assignment, followed by in-lab activities, and complimented by post-lab assignment. In-lab activities involve field trips, experiments, observation stations, or problem sets. Post-lab assignments include online quizzes, problem sets, or laboratory summary reports.